Minimising Copper Activation of Iron Sulfide Minerals during Grinding (International Mineral Processing Congress, 2014)
High flotation of iron sulfide minerals at high pH values in copper ores is mainly due to the activation of these minerals by copper species dissolved from copper sulfide minerals during grinding. Several methods have been tested to reduce this copper activation during grinding and therefore to depress iron sulfide flotation. They include grinding the minerals at high pH values or with a less reactive medium such as high chrome, and addition of a thiol collector or copper complexant during grinding. The efficacy of these methods in the flotation of a copper ore was tested against more common methods of depression of iron sulfide flotation. The mechanism of iron sulfide depression in these methods was also investigated.